Improving Motor Skills of Elementary School Students Through Football Games for Children - Diyana, Kurnia Neta; Adani, Hilmi; Zumriyah, Nur Wakhidah (Yayasan Insan Mulia Bima, 2025)
Motor skills are an important aspect in the development of primary school children, which can be improved through fun physical activities such as soccer games. This game is not only interesting for children, but also plays a role in the development of gross motor (walking, running, jumping, kicking) and fine motor (concentration, eye-hand coordination, and ball control). This study aims to identify the effect of soccer games on the motor skills of elementary school children. The method used was a literature study with a descriptive qualitative approach. The literature reviewed was selected by purposive sampling based on relevance, currency (maximum of the last 10 years, except classical theory), and academic credibility. The research instrument was a literature guide compiled based on motor development indicators. Data were collected through searches on scientific databases such as Google Scholar, Science Direct, and university digital libraries. Data analysis was conducted using content analysis techniques, namely reading, categorizing, comparing, and compiling thematic synthesis from various sources. Results show that soccer games are effective in improving muscle strength, agility, balance, and social skills through teamwork. Therefore, soccer games are recommended as learning media in physical education in elementary schools as well as in daily play activities to support children's optimal motor development.